Wanope Ikuji: Analisis Peran Tradisional Dan Konflik Patriarki Dalam Masyarakat Jepang - Gunawan, Beby Fitri Xaviera (KIRYOKU, 2024)
This study aims to explore traditional roles in "wanope ikuji" or single-operation childcare in Japan, shaped by the dominant patriarchal structure. Using a qualitative approach with a literature analysis method, the primary source of this study includes an exclusive interview conducted by Abema News on June 11, 2024, involving three mothers in Japan. The findings reveal that the patriarchal cultural system remains deeply entrenched in Japan. Key evidence includes the difficulty Japanese mothers face in seeking employment opportunities after childbirth and childcare. For working mothers, balancing childcare responsibilities and professional duties is extremely challenging. Conversely, Japanese men encounter structural barriers, such as societal norms that informally discourage them from taking parental leave. This indicates that traditional childcare patterns, emphasizing the mother as the primary caregiver, remain strongly embedded. To address the tensions between gender equality and traditional childcare roles, Japanese society must adapt to new realities. Measures that can be taken include raising awareness and education about gender equality within households, developing family-friendly work policies that support work-life balance, and shifting social norms to recognize and encourage the active role of fathers in childcare. By implementing these measures, Japan can foster an environment that better supports gender equality and a fairer division of childcare responsibilities.